Correction procedure applied to a single real transformation matrix -Untransposed three-phase transmission line cases - Prado, A. J. [UNESP]; Filho, J.Pissolato; Kurokawa, S. [UNESP]; Bovolato, L. F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
Clarke's matrix has been used as an eigenvector matrix for transposed three-phase transmission lines and it can be applied as a phase-mode transformation matrix for transposed cases. Considering untransposed three-phase transmission lines, Clarke's matrix is not an exact eigenvector matrix. In this case, the errors related to the diagonal elements of the Z and Y matrices can be considered negligible, if these diagonal elements are compared to the exact elements in domain mode. The mentioned comparisons are performed based on the error and frequency scan analyses. From these analyses and considering untransposed asymmetrical three-phase transmission lines, a correction procedure is determined searching for better results from the Clarke's matrix use as a phase-mode transformation matrix. Using the Clarke's matrix, the relative errors of the eigenvalue matrix elements can be considered negligible and the relative values of the off-diagonal elements are significant. Applying the corrected transformation matrices, the relative values of the off-diagonal elements are decreased. The comparisons among the results of these analyses show that the homopolar mode is more sensitive to the frequency influence than the two other modes related to three-phase lines. © 2006 IEEE.
Keywords: Clarke's matrix; eigenvalue; eigenvector; frequency; mode domain; transformation matrix; transmission lines; Eigen-value; Mode domain; Transformation matrices; Transmission line; Eigenvalues and eigenfunctions; Electric lines; Errors; Transmission line theory; Linear transformations